Molecular survey and phylogenetic analysis of Babesia vogeli in dogs - Abdelfattah Selim (Scientific Reports, 2022)
Abstract Canine babesiosis is a life-threatening haemoparasitic disease in dogs that is prevalent worldwide. In this study, the prevalence of Babesia vogeli (B. vogeli) was investigated in dogs from Egypt by using Polymerase Chain Reaction (PCR) assay, and associated risk factors were evaluated. In addition, phylogenetic position of B. vogeli Egyptian isolate was determined by sequencing. A total of 275 blood samples were taken from dogs located in four governorates belonging to the north of Egypt. Samples were examined by PCR targeting the B. vogeli 18S rRNA gene and this species was also confirmed by sequencing. Overall, the prevalence of B. vogeli was 5.1% among the studied dogs and the highest prevalence rate was found in the Giza governorate. Univariate logistic regression was used to evaluate each variable individually. The results revealed a significant association between the prevalence of B. vogeli infection and whether or not dogs were infested with ticks and the type of floor used in dog shelters. Additionally, tick infestation (OR 6.1, 95% CI 1.2–31.4), and living in shelters with soil floors (OR 3.8, 95% CI 0.8–17.8) were identified as potential risk factors for B. vogeli infection. Phylogenetic analysis was performed using B. vogeli 18S rRNA partial sequences with the hypervariable V4 region from GenBank. The Egyptian isolate was assigned to second sub-cluster with B. vogeli isolates from Japan, Venezuela and Paraguay within the B. vogeli/B. canis cluster. The present data will be useful to improve the understanding of canine babesiosis epidemiology and ways to control the disease in companion dogs.